New job and interview alert through Short Message Service (SMS) - Ahmed, Abu Rafi; Shahriar, Shaharat; Rahman, Moshfiqur (BRAC University, 2010)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2006.